PROBLEMS AND TEACHING SOLUTIONS FOR STUDENTS’ IN LEARNING ENGLISH - Sandra Gunawan; Haris Saputra (PROJECT (Professional Journal of English Education), 2020)
ABSTRACTThe Indonesian government has recognized the importance of English by including it in the education system for five decades. English has been integrated into secondary school for a long time. English exerts a stronger influence in the modern world and has become an international language. There are also advantages to introducing foreign languages to young students. Therefore, the Indonesian government made a policy to introduce English starting, elementary, middle and high school. At Katapang 1 Junior High School, this policy is optional. That depends on the demands of the school and the community. Schools and communities are responsible for providing teachers, curriculum and facilities. The teacher is one of the most important parts of the educational discourse and teaching and learning process in school. The two research questions formulated are: 1) what problems are faced by teachers in teaching? 2) how they find out the solutions? These questions urged the study to conduct a research at Katapang 1 junior high school. Three English teachers were chosen as respondents.  In qualitative descriptive method, the interview was implemented to collect the data.  As a result the teachers believe that providing good teaching materials can increase positive outcomes for student, the implementation program for teaching English at Katapang 1 Junior High School was very good as a stage of introducing foreign languages before they continued to higher education. Keywords: English teaching, problems, solutions